Pengujian Aplikasi Reservasi Lapangan Futsal Grogol Depok Dengan Metode Black Box Testing Menggunakan Teknik Boundary Value Analysis - Muhamad Febriyanto; Baresi Bahtiar; Bernice Tiaravitta Theresia; Deni Pratama Setiabudi1; Dwi Noor Saputra; Ahmad Fauzi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The futsal court reservation application is an application that allows users and futsal court owners to more easily access without having to install additional applications that reduce the memory capacity on their smartphone. Before being used, this futsal field reservation application needs to be tested. Testing is a verification process for assessing the quality of a device software and see whether the software meets the expected processes and valid or not. The process that is not optimal can cause inequality of data to be stored in the database .. Testing is done by the Black Box Testing method. In black box testing there are several testing techniques, one of them is Boundary Value Analysis. The Boundary Value Analysis technique performs testing based on the maximum and minimum number of digits to produce valid and invalid values. The first stage carried out in this research is to identify the form functionality to be processed, ensuring the maximum and minimum number of characters entered. The results of testing the futsal field reservation application with the black box testing method with the Boundary Value Analysis technique are the quality of the software is in accordance with the function, and can be utilized properly by the user.